Review of David Novak. 2013. Japanoise: Music at the Edge of Circulation. Durham, NC: Duke University Press. - García Molina, Andrés (Current Musicology, 2014)
First, a disclaimer: this is not a review if “book review” implies the exis-tence of an explicit map or the provision of a summary of sorts. Japanoise is an extraordinary book that requires something else, a different strategy. Just like a project around Noise with a capital N (a musical genre), and noise (a more general concept), required from David Novak a different kind of engagement, a different kind of listening, a different kind of writ-ing. Novak’s Japanoise, based on over ten years of fieldwork in Japan and North America,provides no transparent, easy definitions, nor does it strive to produce a definitive history of Noise in any sense, whether as genre or metaphor. And while Novak’s work pushes towards an approximation to Noise as a potent critique of many things (some of which will be addressed in this review), in Japanoise he manages to investigate generative questions around Noise without merely opposing it to other categories (like music, signal, or information), enacting an all–out critique of a tendency to define objects and subjects too neatly in ethnomusicological and anthropologi-cal research. In Novak’s hands, Noise can refer to an underground genre of music, forms of circulation, a commodity, and everyday techniques of creating and listening.